Uwb-Ofdm System Model for Breast Cancer Detection - Soto-Gomez, J (IEEE, 2022)
This research paper proposes a communication system that can be applied in diagnosis through medical imaging. The objective is to spot abnormalities in breasts with a high level of precision, allowing for diagnostics in the early stages of potential breast cancer. The system was theoretically modeled and simulated with the help of computational calculations. This solution gathers characteristics from different technologies and standards that were combined to model an efficient system which meets the necessary requirements and functions for a feasible and viable proposal for its future implementation. The main contribution of this work is identified in the experimental results through the application of the finite difference method in the time domain (FDTD) where it is shown how a malignant tissue (tumor) reflects to a greater extent the expenditure that falls on said region in compared to healthy tissue made up of fibrous tissue, connective, glandular and adipose tissue. It is also important to highlight the spectral and energy efficiency of OFDM systems, characteristics that directly affect the quality level of the systems. Finally, a simulation of the image formation is performed using an innovative method of spatial filtering under the concept of beamforming.
Keywords: cancer; electric permittivity; orthogonal frequency division multiplexing; chirp; beamforming